Academic Stress, General Health and Life Satisfaction among College Students - Ms. Yashika Dureja; Dr. Roopali Sharma (International Journal of Indian Psychȯlogy, 2022)
The present study was conducted on the Academic stress, general health and life satisfaction among college students. Sample of 100 college students were selected by employing simple random sampling. Objectives of the study: (1) To study the relationship between life satisfaction and academic stress among male and female college students. (2) To find out the relationship between life satisfaction and general health among male and female college students. (3) To measure relationship between academic stress and general health among male and female college students. (4) To find out the difference on the level of academic stress, general health and life satisfaction among male and female college students. (Academic Stress Scale), (General Health Questionnaire 12), (Life Satisfaction Scale) were employed in the present study. For the purpose of drawing out the result, statistical techniques are used which includes correlation and t-test. After analysing the data, the study explored gender differences in academic stress, life satisfaction, and general health among college students. Results showed that academic stress had a significant negative relationship with life satisfaction among female students, but not among males. Female students also showed a significant negative correlation between life satisfaction and general health, a pattern not seen in males. Both genders had a significant positive correlation between academic stress and general health, suggesting higher stress was linked to poorer health. Female students experienced higher academic stress and worse general health than males, but life satisfaction levels were similar across genders. This suggests that, although there were gender-based differences in academic stress and general health, life satisfaction remained consistent across both groups.